2018
DOI: 10.12662/2317-3076jhbs.v7i1.2170.p97-100.2019
|View full text |Cite
|
Sign up to set email alerts
|

Fenilcetonúria associada à alergia à proteína do leite de vaca

Abstract: Introdução: a fenilcetonúria (PKU) é uma doença do metabolismo da fanilalanina cujo tratamento se baseia na introdução precoce de uma fórmula com restrição de fenilalanina. Relato do caso: uma menina, com diagnóstico de PKU a partir da triagem neonatal, com 82 dias de vida, recebeu tratamento dietético com fórmula com restrição de fenilalanina associada à fórmula láctea e desenvolveu alergia à proteína do leite de vaca (APLV) com sintomas cutâneos e gastrointestinais. Conclusão: o manejo dietético da PKU pode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Sixty-four of the 79 included studies reported at least one patient-important outcome at individual or population level, and they are displayed in Table 1 for study characteristics. Regarding study design, 18 were case series [ 22 , 23 , 33 , 34 , 40 – 42 , 45 , 54 , 55 , 58 , 60 , 70 , 84 – 87 ], 47 cross-sectional studies [ 6 , 7 , 13 – 15 , 17 – 21 , 24 , 26 , 29 , 30 , 35 – 39 , 43 , 46 , 47 , 53 , 56 , 59 , 61 , 62 , 67 , 68 , 71 , 73 , 75 – 77 , 79 – 81 , 88 – 91 ], 13 case reports [ 34 , 44 , 48 , 51 , 63 , 64 , 69 , 74 , 84 , 87 , 92 – 94 ], and two cohort studies [ 57 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixty-four of the 79 included studies reported at least one patient-important outcome at individual or population level, and they are displayed in Table 1 for study characteristics. Regarding study design, 18 were case series [ 22 , 23 , 33 , 34 , 40 – 42 , 45 , 54 , 55 , 58 , 60 , 70 , 84 – 87 ], 47 cross-sectional studies [ 6 , 7 , 13 – 15 , 17 – 21 , 24 , 26 , 29 , 30 , 35 – 39 , 43 , 46 , 47 , 53 , 56 , 59 , 61 , 62 , 67 , 68 , 71 , 73 , 75 – 77 , 79 – 81 , 88 – 91 ], 13 case reports [ 34 , 44 , 48 , 51 , 63 , 64 , 69 , 74 , 84 , 87 , 92 – 94 ], and two cohort studies [ 57 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Forty of the included studies were conducted in Brazil [ 14 , 19 – 24 , 26 , 27 , 29 , 31 , 43 , 45 , 51 , 56 , 58 , 59 , 62 , 64 , 67 , 69 – 73 , 75 – 78 , 80 , 81 , 83 , 84 , 86 , 88 , 91 , 94 , 97 , 98 ], seven in Argentina [ 15 , 17 , 18 , 33 – 38 , 46 , 47 ], five in Chile [ 39 42 , 89 ], three each in Colombia [ 48 , 54 , 74 ] and Mexico [ 55 , 85 , 93 ], two each in Ecuador [ 44 , 92 ], Venezuela [ 60 , 63 ] and Uruguay [ 32 , 90 ], and one in Cuba [ 68 ]. One study [ 87 ] was a multicenter conducted in Ecuador, Bolivia, and Paraguay.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations